A mathematical model to predict the porosity and compressive strength of pervious concrete based on the aggregate size, aggregate‑to‑cement ratio and compaction effort - Sathushka Heshan, W.; Thirugnasivam, S.; Daniel Niruban, S.; Sathiparan, N. (Springer, 2023)
The purpose of this study is to explore how characteristics of pervious concrete, such as porosity and compressive strength, are affected by three factors: aggregate size, aggregate-to-cement ratio and compaction effort. The study used three aggregate sizes (5–12 mm, 12–18 mm and 18–25 mm), five different aggregate-to-cement ratios (3.0, 3.5, 4.0, 4.5 and 5.0) and seven different levels of compaction effort (0, 15, 30, 45, 60, 75 and 90 blows). A total of 15 mix designs were used to cast 630 pervious concrete cubes, which were then tested for porosity and compressive strength. The test data were analysed to establish mathematical relationships between the three factors and the two characteristics of pervious concrete. The models accurately predicted the porosity and compressive strength based on the aggregate size, aggregate-to-cement ratio and compaction effort. These models can be useful for practitioners and researchers in optimizing pervious concrete mix designs for various applications.
Keywords: Pervious concrete; Compaction; Aggregate size; Porosity; Compressive strength